A potência estética e humanizadora do contador de histórias - Vasconcelos, Roger Andrei de Castro (My University, 2024)
The act of telling is a way of registering and sharing human experience and culture to generations. In Brazil, since the creation of PROLER, the way of promoting literature through storytelling has been gaining strength and becoming a form of cultural mediation. In this context, it is questioned: how is the aesthetic power of storytelling manifested in the vision of professional storytellers? To answer this question, it was established as a general objective to investigate storytelling as an activity endowed with aesthetic power, from the figure of professional storytellers. To account for the guiding question and the set objective, were analyzed, based on interviews, trajectories of professionals who implemented the PROLER in Brazil as well as storytellers who work in Rio Grande do Sul and who integrated the ProjectSemeando Histórias, approved in the Public Notice 09/2020, of SEDAC/RS, observing practices, procedures and strategies employed in the art of storytelling. The research is characterized as qualitative. The data were constructed from interviews and videos of storytelling in addition to the researcher?s experience, who has been a professional storyteller for 29 years. The analysis of the constructed data was inspired by the principles of content analysis of Bardin (1977) and the results were discussed in the light of Benjamin (1994), Petit (2009) and Zumthor (2018). The research results reiterated that the act of storytelling mobilizes people, in order to show that there is aesthetic power in the process of cultural mediation. In storytelling as art, the storyteller, the chosen story, the scenario and the interlocutors are in tune, among other points. Just as the trees disperse their seeds, the storytellers, with their performance, "emancipate" narratives, providing that the stories survive beyond their own tellers, as the seeds surpass the tree that originated them. [resumo fornecido pelo autor]
O contar é uma forma de registrar e partilhar a experiência e a cultura humana às gerações. No Brasil, desde a criação do PROLER, o modo de compartilhar a literatura pela contação de histórias vem ganhando força e se configurando como uma forma de mediação cultural. Nesse contexto, questiona-se: como se manifesta a potência estética da contação de histórias na visão de contadores profissionais? Para responder esta pergunta, estabeleceu-se como objetivo geral investigar a contação de histórias como uma atividade dotada de potência estética, a partir da figura do contador de histórias profissional. Para dar conta da questão norteadora e do objetivo estabelecidos, foram analisadas, com base em entrevistas, trajetórias de profissionais que implementaram o PROLER no Brasil bem como de contadores de histórias que atuam no Rio Grande do Sul e que integraram o Projeto Semeando Histórias, aprovado no Edital 09/2020, da SEDAC/RS, observando práticas, procedimentos e estratégias empregadas na arte da contação de histórias. A pesquisa caracteriza-se como qualitativa. Os dados foram construídos a partir de entrevistas e de vídeos de contações de histórias mesclados com a experiência do pesquisador, que é contador de histórias profissional há 29 anos. A análise dos dados construídos foi inspirada nos princípios da análise de conteúdo de Bardin (1977) e os resultados foram discutidos à luz de Benjamin (1994), Petit (2009) e Zumthor (2018). Os resultados da investigação reiteraram que o ato de contação de histórias mobiliza as pessoas, de modo a evidenciar que há potência estética no processo de mediação cultural. Na contação como arte, estão em sintonia, entre outros pontos, o contador, a história escolhida, o cenário e os interlocutores. Tal como as árvores dispersam suas sementes, os contadores, com sua performance, "emancipam" narrativas, propiciando que as histórias sobrevivam além de seus próprios contadores, como as sementes ultrapassam a árvore que as gerou. [resumo fornecido pelo autor]
Keywords: Contadores de histórias; Arte de contar histórias.; Educação; Leitura; Story tellers; Education; Learning; National Reading Incentive Program (Brazil)